PERTANGGUNGJAWABAN HUKUM TENAGA MEDIS DALAM KASUS MALAPRAKTIK BERDASARKAN UNDANG-UNDANG NOMOR 29 TAHUN 2004 TENTANG PRAKTIK KEDOKTERAN DAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN - Gunawan Widjaja (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study discusses the forms of legal liability of medical personnel in cases of malpractice based on Law Number 29 of 2004 concerning Medical Practice and Law Number 36 of 2009 concerning Health using a normative-legal literature review method. The analysis reveals that the legal liability of medical personnel is multidimensional, encompassing civil, criminal, and administrative domains. In practice, the resolution of medical malpractice cases in Indonesia still faces various challenges, such as overlapping regulations, a heavy burden of proof on patients, and disparities in access to evidence and legal assistance. The resolution mechanism through the Indonesian Medical Disciplinary Council (MKDKI) has not been fully effective because its decisions are not legally binding. Therefore, regulatory harmonisation, strengthening the role of disciplinary bodies, and improving access to justice for patients are necessary to create a fair and just legal accountability system for all parties.